The Image of Children in Roald Dahl's Matilda - Faradilla, Aina Noor Ade; Hakim, Arief Rahman (English Department, Faculty of Humanities, Andalas University, 2023)
his research aims to explore the image of the children as it is constructed by the educational institution particularly by the teachers in the novel Matilda. This research is a descriptive qualitative study with applies the theory of imagology by Milan Kundera and the image of the child by Loris Malaguzzi. This research used the close textual analysis method to describe and analyze the meaning, structure, and function contained in the text. The result of this research shows that the different images of the children constructed by two teacher characters of the novel. The image of the children constructed by Miss Honey is that the children are innocent, potential, and dependent. While the image of the children constructed by Mrs. Trunchbull is that children are a source of trouble, disgusting, disturbing, and should not exist in the world. Based on the image of the children constructed by Miss Honey and Mrs. Trunchbull, these two teacher figures show different behaviors when they interact with children. Miss Honey tends to pay special attention to children, teach them new things in a fun way, and be open to children. While Mrs. Trunchbull shows abusive behavior in children such as shouting, cursing, and giving harsh punishments to children. Therefore, based on the results of research conducted, it can be concluded that the image of children is not always the same in the eyes of everyone and the image they construct in children affects the way they treat children.